2002
DOI: 10.1603/0022-0493-95.4.820
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and Cross-Resistance to Four Insecticides in Populations of Obliquebanded Leafroller (Lepidoptera: Tortricidae)

Abstract: Populations of obliquebanded leafroller, Choristoneura rosaceana (Harris), were collected from organic and conventionally managed orchards located in the Okanagan and Similkameen Valleys of British Columbia Neonate F1 progeny were assayed for resistance to azinphosmethyl, tebufenozide, methoxyfenozide, and indoxacarb using a leaf disk bioassay. Significant differences in resistance levels among populations were observed for all four insecticides. Insects collected from organic sites were more susceptible to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
56
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 15 publications
5
56
1
Order By: Relevance
“…In the same vein, it can be noted that increased resistance against dibenzoylhydrazine analogs in insect larvae always is accompanied by cross-resistance against other insecticides that have a different mode of action (Wearing, 1998;Waldstein and Reissig, 2000;Smirle et al, 2002;Smagghe et al, 2001;Moulton et al, 2002;Gore and Adamczyk, 2004;Cao and Han, 2006). These findings indicate at increased metabolism or decreased penetration/absorption as the main mechanism of resistance in larvae.…”
Section: Discussionmentioning
confidence: 98%
“…In the same vein, it can be noted that increased resistance against dibenzoylhydrazine analogs in insect larvae always is accompanied by cross-resistance against other insecticides that have a different mode of action (Wearing, 1998;Waldstein and Reissig, 2000;Smirle et al, 2002;Smagghe et al, 2001;Moulton et al, 2002;Gore and Adamczyk, 2004;Cao and Han, 2006). These findings indicate at increased metabolism or decreased penetration/absorption as the main mechanism of resistance in larvae.…”
Section: Discussionmentioning
confidence: 98%
“…Spindler-Barth and Spindler (1998) reported that cells of C. dilutus selected in the presence of 20E were resistant only to the moulting hormone, but still responded to tebufenozide, whereas subclones selected in the presence of tebufenozide showed cross-resistance to 20E. Related to the in vivo system, some cross-resistance has been reported between dibenzoylhydrazinetype insecticides and other insecticides in many insects (Sauphanor and Bouvier, 1995;Wearing, 1998;Waldstein et al, 1999;Moulton et al, 2002;Smirle et al, 2002;Cao and Han, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This reliance on insecticides has resulted in the development of resistance to azinphosmethyl in some orchard populations of C. rosaceana (Smirle et al 2002); A. argyrospila resistance to diazinon and azinphosmethyl was documented in 1977 and 1984, respectively (Madsen andCarty 1977, Vakenti et al 1984). Insecticide resistance in populations of C. rosaceana has also been reported from several apple-producing regions of eastern North America (Reissig et al 1986, Carriè re et al 1996, Pree et al 2001, including resistance to the recently introduced insect growth regulator (IGR) tebufenozide (Waldstein et al 1999).…”
mentioning
confidence: 99%
“…In populations of C. rosaceana from New York State, Waldstein and Reissig (2000) reported resistance to several materials with novel modes of action, even if they had not been used previously in the orchards where the insects had been obtained. Smirle et al (2002) documented signiÞcant levels of resistance to indoxacarb (Avaunt, DuPont, Wilmington, DE) in populations of C. rosaceana from British Columbia. Indoxacarb is not registered for use in Canadian orchards, and the insects tested had no prior exposure to the compound.…”
mentioning
confidence: 99%
See 1 more Smart Citation